Hutchison's Clinical Methods Clinical Methods - Swash, Micheal (London W.B. Saunders, 1995)
Royal London Hospital, U.K. Twentieth edition of a textbook for medical students on clinical examination and history-taking. Previous edition 1989. New topics include the endocrine system and metabolic disorders, examining the elderly, and ethical issues. Illustrated. 20 U.K. contributors.
Keywords: Clinical medicine